Kink macroinstabilities and resistive layer structure of internal kinks in cylindrical plasma - Gurin, A.A. (Вопросы атомной науки и техники, 2009)
Eigen-frequencies and shapes of the non-local magnetic kink-modes m=1, n>1 in a field reversal pinch are obtained in cylindrical force-free approximation by shooting method. The mode profile and the resistive layer containing the resonant surface of the internal kinks are calculated numerically. Instability is revealed, both for external and internal modes, which is not effected by resistive layer in plasmas with high conductivity, it is determined by the current gradient due to the high paramagnetic parameter in the pinch core. Сформульована крайова задача та чисельним методом стрільби визначені власні частоти й профілі гвинтових кінк-мод m=1, n>1 в пінчі з оберненим полем. В циліндричному наближенні розраховані профілі нелокальних мод, включно з резистивними шарами в разі внутрішніх мод. Доведена нестійкість мод в плазмі з великою провідністю, яка визначається градієнтом струму й не пов’язана безпосередньо з наявністю резистивного шару внутрішніх мод у плазмі з великою провідністю. Сформулирована краевая задача и численным методом стрельбы определены собственные частоты и профили винтовых кинк-мод m=1, n>1 в пинче с обращенным полем. В цилиндрическом приближении рассчитаны профили нелокальных мод, включая резистивные слои в случае внутренних мод. Показана неустойчивость мод в плазме с высокой проводимостью, которая определяется градиентом тока и не связана непосредственно с наличием резистивных слоев внутренних мод в плазме с высокой проводимостью.